Comparison of Analytic Hierarchy Process and Frequency Ratio Methods in Landslide Susceptibility Analysis: Example of Akçaabat and Düzköy districts of Trabzon province - Melek Dalkes; Mehmet Seren Korkmaz (Doğal Afetler ve Çevre Dergisi)
Landslides are one of the leading natural disasters in the Black Sea Region of Türkiye. Trabzon is the province where the most landslides occurred in the country. Landslide susceptibility maps should be prepared in order to predetermine the areas with high landslide susceptibility in order to minimize the losses due to landslides. In this study, landslide susceptibility analysis is performed, and landslide susceptibility maps are produced to reveal the areas with high landslide susceptibility within the boundaries of Akçaabat and Düzköy districts of Trabzon province using Analytical Hierarchy Process (AHP) and Frequency Ratio (FR) methods. ArcGIS for Desktop, one of the Geographic Information Systems (GIS) platforms, is used for landslide susceptibility analysis. Geographical data are obtained from public institutions and open access online sources. The data are spatially organized according to the study area and purpose by various GIS tools. A total of 13 criteria which are respectively; slope, curvature, lithology, precipitation, aspect, topographic wetness index (TWI), distance to rivers, distance to highways, distance to fault lines, land use, soil type, elevation and normalized difference vegetation index (NDVI) for landslide susceptibility are evaluated as effective to cause landslides as a result of the literature review. Pairwise comparisons are made to determine the importance of the effects of each criterion on landslide formation and the weights between the criteria by using the AHP method. Then a landslide susceptibility map is produced according to the AHP method. In addition, a landslide susceptibility map was produced according to the FR method using the landslide inventory records obtained from responsible institutes of the country. It is noticed that the FR method produced more realistic results than the AHP method in terms of determining the locations of the landslides observed in the study area when the maps produced by both methods are compared.